Production of phi and F(1970)--> phi pi in e+e- annihilation at 29 GeV. - Derrick, M; Fernandez, E; Fries, R; Hyman, L; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; Wood, D; et al. (1985)
Data from the high-resolution spectrometer at PEP have been used to study the inclusive production of mesons and F mesons decaying into . Fragmentation functions and cross sections are presented and compared to existing data. The total cross section at 29 GeV is 406 pb. The observed F signal in the region z>0.4, given the assumption that R(F)[R(F)+R(D)]=0.15, corresponds to an F branching ratio of (3.31.1)%. The measured F mass is 196333 MeV/c2. © 1985 The American Physical Society.